A correction method for Vickers indenters squareness measurement due to the tilt of the pyramid axis. (July 2019) - Prato, Andrea; Galliani, Davide; Origlia, Claudio; Germak, Alessandro
Highlights: Correction of Vickers indenters squareness measurement due to axis tilt is proposed. Application of correction method to experimental tests improves accuracy. The method is suitable on different measuring systems and can improve the standards. Abstract: In ISO 6507-3 it is required that the quadrilateral base of Vickers indenter has angles of 90° ± 0.2°. Squareness angles are usually evaluated through optical techniques by measuring the angles between two consecutive faces, which correspond to the quadrilateral base angles when the axis of the pyramid is perfectly parallel to the indenter-holder axis. However, if the pyramid axis is tilted by an angle within 0.3°, as allowed by the standard, these angles no longer correspond. This work deals with the description of a numerical method, based on a proper geometrical model, to correct squareness measurements. The proposed method is applied to experimental tests and measurement results, with related uncertainties, are presented. It is shown that the accuracy is improved. This method is easily implementable on different measuring systems and can be internationally adopted to improve the relevant standard.